2005
DOI: 10.1021/es051342d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Glyphosate and Aminomethylphosphonate by Manganese Oxide

Abstract: Glyphosate (N-(phosphonomethyl)glycine), the most commonly used herbicide worldwide, degrades relatively rapidly in soils under most conditions, presumably by microbial processes. The most frequently detected degradation product in soil and water is AMPA (aminomethylphosphonic acid). We report the first evidence for an abiotic pathway of glyphosate and AMPA degradation under environmentally realistic conditions. Both glyphosate and AMPA degraded at 20 degrees C in dilute aqueous suspensions of birnessite, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
156
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 18 publications
13
156
4
Order By: Relevance
“…The continuous oxidation of glycine produced glycolic acid and NH 3 -N. Meanwhile, Mn 2+ ions were released into the aqueous solution. Similar intermediates (i.e., sarcosine, glycine, and formic acid) were observed in the degradation of glyphosate by using manganese oxide [14]. In the electro-MnO 2 process, sarcosine, glycine and PO 3À 4 were also identified in the initial phase of reaction.…”
Section: Proposed Reaction Pathwayssupporting
confidence: 57%
See 1 more Smart Citation
“…The continuous oxidation of glycine produced glycolic acid and NH 3 -N. Meanwhile, Mn 2+ ions were released into the aqueous solution. Similar intermediates (i.e., sarcosine, glycine, and formic acid) were observed in the degradation of glyphosate by using manganese oxide [14]. In the electro-MnO 2 process, sarcosine, glycine and PO 3À 4 were also identified in the initial phase of reaction.…”
Section: Proposed Reaction Pathwayssupporting
confidence: 57%
“…It has been reported that both glyphosate and AMPA could be degraded in dilute aqueous suspensions of birnessite, a manganese oxide common in soils, as evidenced by the accumulation of orthophosphate in solution [14,15]. In the oxidation of glyphosate using MnO 2 , the oxidation efficiency was low and a large portion of Mn 2+ ions were released [16] …”
Section: à2mentioning
confidence: 99%
“…Well-drained soils may also contain these minerals due to previous wet conditions (McKenzie, 1989). Manganese III and IV minerals can mediate the transformation of numerous organic compounds, including herbicides (Barrett & McBride, 2005) and antibiotics (Zhang & Huang, 2005;Rubert & Pedersen, 2006).…”
mentioning
confidence: 99%
“…The efficiency of GH mineralization reached values around www.intechopen.com 60%. Barret & Mcbride (2005) have evaluated the oxidative degradation of GH on manganese oxide. There was no significant herbicide degradation (10 mg L -1 ), and much of the herbicide simply adsorbed onto the manganese oxide.…”
Section: Glyphosate Contaminationmentioning
confidence: 99%